Cherry Valley Ducks Mitochondrial Antiviral-Signaling Protein-Mediated Signaling Pathway and Antiviral Activity Research - Li, Ning; Hong, Tianqi; Li, Rong; Wang, Yao; Guo, Mengjiao; Cao, Zongxi; Cai, Yumei; Liu, Sidang; Chai, Tongjie; Wei, Liangmeng (Frontiers in Immunology, 2016)
Mitochondrial antiviral-signaling protein (MAVS), an adaptor protein of retinoic acid-inducible gene I (RIG-I) like receptors (RLRs)-mediated signal pathway, is involved in innate immunity. In this study, Cherry Valley duck MAVS (duMAVS) was cloned from the spleen and analyzed. duMAVS was determined to have a caspase activation and recruitment domain at N-terminal, followed by a proline rich domain and a transmembrane domain at C-terminal. Quantitative real time PCR indicated that duMAVS was expressed in all tissues tested across a broad expression spectrum. The expression of duMAVS was significantly up-regulated after infection with duck Tembusu virus. Overexpression of duMAVS could drive the activation of interferon-β, nuclear factor-κB, interferon regulatory factor 7, and many downstream factors (such as Mx, PKR, OAS, and IL-8) in duck embryo fibroblast cells. What’s more, RNA interference further confirmed that duMAVS was an important adaptor for IFN-β activation. The antiviral assay showed that duMAVS could suppress the various viral replications (duck Tembusu virus, novel reovirus, and duck plague virus) at early stages of infection. Overall, these results showed that the main signal pathway mediated by duMAVS and it had a broad-spectrum antiviral ability. This research will be helpful to better understanding the innate immune system of ducks.